Consumers buying decision on frozen traditional cakes in Kedah - Wan Anuar, Wan Nuranisa Syafika (2018)
Traditional Frozen Cakes products are the new innovation for making the cakes available in frozen state. The innovation on the products has bring convenience to the consumer’s consumptions. Therefore, the consumer preference has change due to the development of the cakes. This study investigated consumers buying decisions on purchasing traditional frozen cakes product. The study was performed by using a structured questionnaires survey which involved 378 respondents around Kedah. There are a few areas selected to do the study which are supermarket, might market, market, mart, frozen food shop and online purchase. The respondents were selected randomly using a cluster sampling methodology. The questionnaires consist of 6 sections of questions which are respondent’s background, purchasing information, respondent’s attitude towards the product, subjective norm, perceived behaviour control and buying decisions. This research aims to better understand how attitudes and beliefs influence consumers buying decision on frozen traditional cakes. The findings of this study indicated that gender, age, race, religion, ancestry, marital status, education level, occupation and income level play an important role in decision making of purchasing. There are three factors that can influence consumer’s buying decisions on frozen traditional cakes which are attitude, subjective norms and perceived behaviour control. Besides, age, marital status, educational level and occupation has the association between buying decisions of frozen traditional cakes among consumers. Other than that, subjective norm shows the most influential factor as compared to the attitude and perceived behaviour control of consumer’s decisions.